PRESCRIPTION AUDIT IN OUTPATIENT DEPARTMENTS OF TERTIARY CARE HOSPITALS; FACTS AND RECOMMENDATIONS - Khan, Muhammad Wasiullah; Khurshied, Saleh; Khurshid, Nawal; Iqbal, Rafay; Khizer, M Azeem; Ahmed, Hammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate written prescriptions according to a checklist based on WHO guidelines (prescription audit). To compare prescriptions of senior and junior physicians and to provide data and recommendations.Study Design: Cross-sectional, analytic study.Place and Duration of Study: Pak Emirates Military Hospital, and Combined Military Hospital, Rawalpindi Pakistan, from March to Aug 2018.Methodology: A total of 205 prescriptions using convenient sampling technique were analyzed according to a checklist based on WHO guidelines for standard prescription writing. Data was analyzed using SPSS-22.Results: Out of total 205 prescriptions, 83 (40%) prescriptions belong to senior and 122 (60%) to junior physicians. Fifty (25%) prescriptions lacked patient name, 49 (24%) lacked age. Gender was mentioned in only 117 (57%) prescriptions. Date, diagnosis and dosage of drug were written in 170 (83%), 172 (84%) and 177 (86%) respectively while dosage form and route of administration were mentioned in 144 (70%) and 102 (50%) respectively. Generic name was written in only 75 (37%) prescriptions. Name and stamp of the doctor were available on 135 (66%) and 125 (61%) prescriptions respectively. A statistically significant association was observed between senior and junior physicians in terms of error in name of patient and dosage form (p=0.002& 0.005 respectively).Conclusions: Prescriptions were mainly deficient in the generic names of drugs. Route of administration was missing in half of the prescriptions. None of the parameters was totally accurate. Prescriptions from junior physicians had more errors.